1991
DOI: 10.1590/s0074-02761991000300008
|View full text |Cite
|
Sign up to set email alerts
|

Displacement of Biomfhalaria glabrata by thiara granifera under natural conditions in the Dominican Republic

Abstract: After a study of the population dynamics of Biomphalaria glabrata snails in several breeding places in the Dominican Republic, the snail Thiara granifera was introduced in some B. glabrata habitats. T. granifera became established in one point in one habitat in the townof Quisqueya, in the east of the country. Around this point of establishment 6 points were selected in order to observe the population dynamics of both species of snails and the chemical and biological characteristics at each point. Four of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…It has been found that T. granifera can reach densities of up to 10,000 individuals/m 2 , displacing most endemic snail species, a ‘foe’ in aquatic biodiversity conservation, as was the case in wetlands in Puerto Rico [ 63 ], Venezuela [ 64 ], and South Africa [ 55 , 65 ]. However, this potentially creates opportunities for biological control against schistosome/ Fasciola -competent snail species, thereby becoming a ‘friend’ from a public health perspective [ 66 , 67 ]. Competitive exclusion might, therefore, explain the absence of endemic snail species at sites where T. granifera is present, especially schistosome-competent snails, which were either scarce or entirely absent in the presence of T. granifera .…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that T. granifera can reach densities of up to 10,000 individuals/m 2 , displacing most endemic snail species, a ‘foe’ in aquatic biodiversity conservation, as was the case in wetlands in Puerto Rico [ 63 ], Venezuela [ 64 ], and South Africa [ 55 , 65 ]. However, this potentially creates opportunities for biological control against schistosome/ Fasciola -competent snail species, thereby becoming a ‘friend’ from a public health perspective [ 66 , 67 ]. Competitive exclusion might, therefore, explain the absence of endemic snail species at sites where T. granifera is present, especially schistosome-competent snails, which were either scarce or entirely absent in the presence of T. granifera .…”
Section: Discussionmentioning
confidence: 99%
“…Further experimental and field studies should be carried out to verify the use of T. granifera as a biological control agent for schistosomiasis in South Africa. In the Caribbean, T. granifera was introduced into waterbodies to compete and displace the native intermediate host snail Biomphalaria glabrata, responsible for Schistosoma mansoni [47][48][49]. A negative correlation was observed between B. tropicus and B. globosus.…”
Section: Discussionmentioning
confidence: 99%
“…Biological control using the phenomenon of competition by non-medically important snails was found to be a cost-effective, low maintenance, popular way of controlling the disease. Competitive action of the ampullarid snail M. cornuarietis through food and predation of eggs and young snails [93] or B. glabrata ’s avoidance of the prolific and rapidly colonizing parthenogenic thiarid snails T. granifera and especially M. tuberculata [94] all resulted in varying levels of displacement of B. glabrata populations. Biological control does have its limits as shown in St Lucia where B. glabrata and M. tuberculata were found to co-exist in many habitats [75], and in Guadeloupe the Thiarid snails were unable to displace B. glabrata in certain areas where rats served as S. mansoni intermediate hosts [54].…”
Section: Research and Control Needsmentioning
confidence: 99%